2014
DOI: 10.1016/j.peptides.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Salivary adiponectin levels are associated with training intensity but not with bone mass or reproductive function in elite Rhythmic Gymnasts

Abstract: Elite Rhythmic Gymnasts (RGs) constitute a unique metabolic model and they are prone to developing Anorexia Athletica. The aim of the present study was to evaluate the effect of training intensity on salivary adiponectin levels and assess a possible role of salivary adiponectin levels as a predictive factor of reproductive dysfunction and bone mass acquisition in elite RGs. The study included 80 elite female RGs participating in the World Rhythmic Gymnastics Championship tournament held in Montpellier, France … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Our results showed that leptin and adiponectin levels remained relatively stable from 7 to 12 years of age in premenarcheal RG. In agreement with leptin results in RG (Jürimäe, 2014), adiponectin was associated with weekly training volume but not with bone mass acquisition in elite RG (Roupas et al, 2014). The longitudinal results of present study confirm that leptin and adiponectin are not directly involved in bone mineral accrual in premenarcheal RG.…”
Section: Discussionsupporting
confidence: 89%
“…Our results showed that leptin and adiponectin levels remained relatively stable from 7 to 12 years of age in premenarcheal RG. In agreement with leptin results in RG (Jürimäe, 2014), adiponectin was associated with weekly training volume but not with bone mass acquisition in elite RG (Roupas et al, 2014). The longitudinal results of present study confirm that leptin and adiponectin are not directly involved in bone mineral accrual in premenarcheal RG.…”
Section: Discussionsupporting
confidence: 89%
“…Nineteen investigations described menstrual disorders in individual sports ( Table 4 ). Most of the studies focused on rhythmic gymnastics [ 30 , 31 , 35 , 36 , 67 , 68 , 69 , 70 , 71 , 72 ], artistic gymnastics [ 72 , 73 ] and gymnastics [ 33 , 34 ]. Menstrual disorders were reported based on the last 12 months [ 33 , 34 , 35 , 36 , 37 , 67 , 68 , 71 , 74 ], the last 3 months [ 30 ], one year after menarche [ 75 ], or in the post-menarche period [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Roupas ND et al (31) no association of salivary adiponectin levels was documented with either reproductive function or bone mass acquisition. Parm A.-L et al (32) found that adiponectin and ghrelin levels did not predict increases in measured bone mineral density (BMD) value in rhythmic gymnasts.…”
Section: Sažetakmentioning
confidence: 89%